PENGARUH MODEL PEMBELAJARAN MULTILITERASI TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS IV SD NEGERI 30 PALEMBANG - Septiana; Aswadi Jaya; Mega Prasrihamni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the impact of implementing a multiliteracy learning model on improving Indonesian language learning outcomes among fourth-grade students at SD Negeri 30 Palembang. This research employs a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The study subjects consist of two classes: one serving as the experimental group and the other as the control group. Data were collected using objective multiple-choice tests to measure students' learning achievement. The data analysis results indicate a significant difference in learning outcomes between the experimental and control groups. The average posttest score of students in the experimental class was 71.94, which was higher than the control class, which had an average score of 52.58. The t-test analysis showed a significance value of 0.001, which is less than α = 0.05. Therefore, H₀ is rejected and Hₐ is accepted. It can be concluded that there is a significant difference between the two groups, and the application of the multiliteracy learning model assisted by audiovisual media has a positive contribution to improving Indonesian language learning outcomes compared to the conventional learning model.